Identification of Cells Expressing Cyclooxygenase-2 in Response to Interleukin-1β in Rat Aortae - Tomoyuki Nakano; Ichiro Wakabayashi (Elsevier, 2010)
Localization of cyclooxygenase-2 (COX-2) in rat aortae was investigated. In endothelium-intact aortic strips stimulated with interleukin-1 β (IL-1 β ), COX-2 was detected in adventitial fibroblasts and macrophages but not in tunica media. IL-1 β−induced COX-2 expression was also detected in medial smooth muscle cells of endothelium-denuded aortae and cultured rat aortic smooth muscle cells. IL-1β−induced COX-2 expression in all of the above cells was abolished in the presence of U0126, an inhibitor of extracellular signal-regulated kinases (ERK). Thus, IL-1β induces COX-2 through the ERK-mediated pathway in adventitial fibroblasts and macrophages of healthy aortae; and in addition, medial smooth muscle cells are also responsible for COX-2 expression in remodeled aortae. Keywords:: cyclooxygenase-2, remodeling, vascular smooth muscle